1989
DOI: 10.3382/ps.0680027
|View full text |Cite
|
Sign up to set email alerts
|

Egg Production and Egg Composition of Parental Lines and F1 and F2 Crosses of White Rock Chickens Selected for 56-Day Body Weight

Abstract: Egg production and weights of eggs and their components were measured in body weightselected lines and in reciprocal F, and F 2 crosses. Nonadditive genetic variation was significant for age at onset of lay; percentage of hen-day ovulations, hen-day egg production, and normal eggs produced; egg weight and shell thickness; percentage of dry yolk and total moisture; shell and yolk dry matter; and ratios of albumen to yolk (A:Y) both on a wet and dry weight basis. There was recombination loss for all of these tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 28 publications
1
6
1
Order By: Relevance
“…Also functional development of testes was more rapid than for ovaries, and females markedly exceeded males in adult BW. The growth and reproduction data from Japanese quail lines selected long term for high BW on optimal (P line) or suboptimal (T line) diet (Marks, 1978(Marks, , 1979 and chicken lines divergently selected for BW (Anthony et al, 1989(Anthony et al, , 1991 further support these findings.…”
Section: Onset Of Sexual Maturity and Growth Curvesupporting
confidence: 70%
“…Also functional development of testes was more rapid than for ovaries, and females markedly exceeded males in adult BW. The growth and reproduction data from Japanese quail lines selected long term for high BW on optimal (P line) or suboptimal (T line) diet (Marks, 1978(Marks, , 1979 and chicken lines divergently selected for BW (Anthony et al, 1989(Anthony et al, , 1991 further support these findings.…”
Section: Onset Of Sexual Maturity and Growth Curvesupporting
confidence: 70%
“…These were higher than mean egg weights for broiler breeds reported by some authors (LECLERQ et al, 1984;ANTHONY et al, 1988;HAGGER, 1993). The slightly higher mean egg weights obtained in this study may have resulted from selection for body weight since egg weight is known to be positively correlated with body size (HALE and CLAYTON, 1965;CLAYTON and ROBERTSON, 1966).…”
Section: Datacontrasting
confidence: 55%
“…The chicken in this study were slightly older at first egg than other meat-type chicken reported in the literature (LECLERCQ et al, 1984;ANTHONY et al, 1988).…”
Section: Datamentioning
confidence: 38%
“…For example, selection for BW has altered the age at onset of lay (Dunnington et al, 1983), follicular development Zelenka et al, 1986), normal egg production (Marks, 1979; and composition (Anthony et al, 1989), carcass composition (Bacon and Nestor, 1983a,b), patterns of feed consumption (Barbato et al, 1980;Darden and Marks, 1989), and feed preference (Huey et al, 1982;Brody et al, 1984). These effects might influence a selection program by limiting the realized selection response.…”
Section: Introductionmentioning
confidence: 96%